Instytucjonalne uwarunkowania modernizacji polskiego rolnictwa po 1989 r. - Zalesko, Elżbieta; Zalesko, Marian (Wydawnictwo Uniwersytetu Rzeszowskiego, 2025)
Artykuł podejmuje problematykę modernizacji polskiego rolnictwa. Analizą objęte zostały przeobrażenia w tym sektorze gospodarki na przełomie XX i XXI wieku. Procesy modernizacji wzbudzają zainteresowanie przedstawicieli różnych nauk społecznych, m.in. ekonomistów czy specjalistów od zarządzania. Ważne jest zatem interdyscyplinarne podejście do wyjaśniania tego zjawiska. Wydaje się, że takie możliwości stwarza ekonomia instytucjonalna, która podkreśla znaczenie instytucji w dynamizowaniu poszczególnych sektorów (w tym rolnego) oraz gospodarki jako całości. Celem opracowania, które ma charakter teoretyczno-empiryczny, jest przedstawienie wybranych instytucjonalnych uwarunkowań procesu modernizacji rolnictwa w Polsce. Do badań autorzy wykorzystali metodę opisową. W ramach przeprowadzonej analizy wykazano, że ważną rolę w obszarze modernizacji sektora rolnego w Polsce odegrały instytucje formalne i nieformalne.

The article is devoted to the issue of the modernisation of Polish agriculture. The analysis covers transformations that took place in this sector at the turn of the 21 st century. Modernisation processes have attracted the interest of representatives of various social sciences, including economists and management specialists. It is therefore important to take an interdisciplinary approach to explaining this phenomenon. Institutional economics, which emphasises the importance of institutions in dynamising individual sectors and the economy as a whole, appears to offer such opportunities. Formal and informal institutions, whose influence has a significant impact on the functioning of th eagricultural sector, play an important role in this regard. The aim of the study, which is theoretical and empirical in nature, is to present the institutional determinants of the agricultural modernisation process in Poland. The authors used the descriptive method for the study.
The institutional conditioning of the modernisation of Polish agriculture after 1989
Keywords: instytucje formalne; instytucje nieformalne; rolnictwo; Polska; formal institutions; informal institutions; agriculture; Poland